A good-governance framework for urban management - Rathin Biswas; Arnab Jana; Kavi Arya; Krithi Ramamritham (Journal of Urban Management, 2019)
The shift towards capacity building and deteriorating governance, may lead to poor service delivery which is a prime challenge for governing agencies. Different countries follow their own sets of governance parameters and often assess the outcome of policies based on them. In order to compose a uniform good governance framework, we have conducted a comparative analysis among 22 existing governance frameworks across the globe and shortlisted 13 major criteria along with 74 sub-criteria. We explored the method to measure these governance components with the help of various indicators and took expert opinion to distribute weight among these indicators. Finally, the case of Mumbai city is discussed with the examples of direct indicators, which may be used to measure a sub-criteria of any specific criteria. The quantification process is also demonstrated with three specific representative indicators. For example- the contribution towards good-governance has been increased from 0.001218 in 2016 to 0.004466 in 2017, for the indicator "conviction percentage of corruption cases" of sub-criterion "active anti-corruption commission" of criterion "accountability". Researchers as well as policymakers will be benefitted with the method demonstrated here, which can help in assessing governance of any public service towards further policy amendments.
Keywords: 710; Governance; Indicator; Management; Public; Urban Services